The complete mitogenome of the Macquarie perch, Macquaria australasica Cuvier, 1830 (Teleostei: Percichthyidae). (2nd January 2016) - Gan, Han Ming; Tan, Mun Hua; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the conservationally significant Macquarie perch ( Macquaria australasica ) was obtained from low-coverage shotgun sequencing using the MiSeq sequencer. The M. australasica mitogenome has 16, 496 base pairs (55% A + T content) made up of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a 819 bp non-coding AT-rich region. This is the first mitogenome sequence for the genus Macquaria, and the third to be reported for the family Percichthyidae.